Two known and one new species of Draconematidae and Epsilonematida (Nematoda, Desmodorida) from the White Sea, North Russia - Fedyaeva, Maria A.; Neretina, Tatjana V.; Konovalova, Olga P.; Tchesunov, Alexei V. (Zootaxa, 2016)
Morphological descriptions of three “walking nematode” species found for the first time in the White Sea are presented. Draconema ophicephalum (Claparède, 1863) (Draconematidae) and Epsilonema steineri Chitwood, 1935 (Epsilonematidae), both known from insufficient material and females only, are re-described and problems of their taxonomic identification as well as species compositions of respective genera are discussed. The new species Prochaetosoma marisalbi sp. n. (Draconematidae) differs from other Prochaetosoma species except P. longicapitatum (Allgén, 1935) in that the pharyngeal bulb lumen is not cuticularised, from P. longicapitatum by shape of body and rostrum, greater number of cephalic adhesive tubes, and from P. maertensi Decraemer, 1989 by having a relatively longer tail, fewer anterior adhesive tubes and longer spicules, besides lacking cuticular thickening in the pharyngeal bulb. Draconema hoonsooi, D. youngeouni, P.rochaetosoma beomseomense, P. brevicaudatum, P. byungilli, P. cracense, P. saheungi, P. sujungi, P. supseomense erected by Rho & Min (2011) are considered as invalid species while Prochaetosoma arcticum, P. lugubre and Epsilonema cygnoides are assumed as species inquirenda. From a phylogenetic tree based on the 18S rRNA gene, all three White Sea species adjoin to unidentified species of their respective genera.